IMPLEMENTASI MANAJEMEN MUTU TERPADU DALAM PENINGKATAN MUTU LULUSAN DI MAN 4 AGAM - Naharuddin, Naharuddin; Sesmiarni, Zulfani (Jurnal Ilmu Pendidikan Islam, 2025)
Quality Management (TQM) in improving the quality of graduates at MAN 4 Agam. The TQM approach is applied to create a holistic, integrated and sustainable education system. This research uses descriptive qualitative methods with data collection techniques in the form of interviews, observation, and documentation. The main focus of the research is on strategies to improve learning quality, Islamic character development, and the challenges and successes of TQM implementation. The results showed that the implementation of TQM at MAN 4 Agam focuses on strengthening the curriculum based on Islamic values, training teachers to improve pedagogical and technological competencies, and implementing innovative learning methods. In addition, the habituation of religious programs such as tahfidz Al-Qur'an, morning halaqah, and congregational worship has contributed to the formation of students' Islamic character. However, the implementation of TQM at MAN 4 Agam also faced challenges, such as budget limitations, resistance to change, and lack of parental involvement. Nevertheless, continuous evaluation and support from various parties have helped overcome these obstacles. This study concludes that TQM is effective in improving the academic and character quality of graduates and can serve as a model for other educational institutions.